Socio-economic, political and international dimensions of Ukrainian crisis - Kurylev, Konstantin P. (Journal of the Belarusian State University. International Relations, 2018)
This article presents the after-effect of the Ukrainian crises for the internal situation of the country, in particular a situation in the social and economic sphere and for the international relations in general. The author notes that the situation in Ukraine, which had turned into a conflict after the power shift in February, 2014, led the national economy to a deep decline, which cannot be overcome under Ukraine’s own power. According to the researcher’s opinion, the main problem of the implementation of Minsk agreements is the different approaches of the signed parties to the fulfillment of their obligations. The article emphasizes that the current Ukrainian crisis in many aspects turned out to be the consequence of the de facto unfinished “cold war”. Mostly because of the West’s efforts Ukraine had to sever the geopolitical and civilization ties with Russia and to choose the “Western project of development”. This choice led the country to its current situation and highlighted an actuate question about the future of the Ukrainian nationhood.